Comparison of sedentary behaviors between children with autism spectrum disorders and typically developing children - Must, Aviva; Phillips, Sarah M.; Curtin, Carol; Anderson, Sarah E.; Maslin, Melissa; Lividini, Keith; Bandini, Linda G. (SAGE Publications, 2014)
Time spent in sedentary behavior is largely due to time spent engaged with electronic screen media. Little is known about the extent to which sedentary behaviors for children with autism spectrum disorder differ from typically developing children. We used parental report to assess and compare time spent in sedentary behaviors for 53 children with autism spectrum disorder and 58 typically developing children aged 3–11 years. We also determined how sedentary behavior was related to child weight status (body mass index z-score). Overall, children with autism spectrum disorder spent an hour more in sedentary behaviors on weekdays compared to typically developing children (5.2 vs 4.2 h, p = 0.03), and most of this difference was due to screen time. The age- and sex-adjusted estimate of weekday total daily screen time was 1.6 h (typically developing) compared to 2.5 h (autism spectrum disorder, p = 0.004 for difference). A significant relationship between BMI z-score and total sedentary behavior time on weekend days was observed among young children with ASD, but not among TD children. The modest association between weekend sedentary behaviour time and BMI z-score among children with ASD suggests that sedentary behaiour is linked to relative weight status in these children. Further research is needed to confirm these findings and identify causal pathways.